Les institutions de la République romaine des origines à la mort d'Auguste - Giovannini, Adalberto (Schweizerische Beiträge zur Altertumswissenschaft, 2015)
This book's presentation of the republican Roman institutions and their history enables the reader to clearly distinguish between what we know from ancient sources and the contemporary knowledge based on modern research. The main goal consists in first presenting the well-documented Roman institutions of the last centuries of the Republic and then analysing the reliability of the ancient sources which deal with the origins of these institutions since the foundation of Rome.